المؤشرات الموضوعية للاستشهادات المرجعية فى أعمال المؤتمرات: دراسة تطبيقية على أعمال المؤتمر الرابع والعشرين للاتحاد العربى للمكتبات والمعلومات "اعلم" - إدريس، منال أحمد عبدالماجد (جامعة النيلين - إدارة البحوث والتنمية والتطوير, 2015)
Subject indicators of citations of conference works: an applied study of the works of the twenty fourth conference of the Arab library and information Association (AL&IA). The objective of this study is to analyze a sample of the citations of the works published in the 24th conference proceedings of the (AL&IA), in order to trace the law of scattering indicators as well as the inter _ disciplinary knowledge. The researchers used the bibliometric and content analysis methods in the context of the case study methods. She also used the "Greater Arabic Subject-heading List" as a standard reference. The citation sample is limited to the Arabic books mentioned among the citations of the conference works. The researcher solicited subject headings from the book titles, and noted the frequency of the appearance of each subject heading in the sample, and then analyzed the data. Some of the important findings are that the analysis of the data assured the validity of Bradford law of scattering, and pointed out the subjects that do highly interplay with the field of library and information science. Some of the important recommendations are: 1. Researcher should observe standard subject headings when they construct the titles of their works. 2. Terms that would be sujested as of potential indexing value should be considered in the revised editions of elevant subject_ heading list. Training the Librarians in the field of technology, administration, and education.
تهدف هذه الدراسة إلى تحليل عينة من الاستشهادات المرجعية الواردة في أعمال المؤتمر الرابع والعشرين للاتحاد العربي للمكتبات والمعلومات (اعلم)، وذلك للكشف عن قوانين التشتت والتداخل البنيوي بين مجال المكتبات والمجالات الأخرى. استخدمت الباحثة المنهج الببليومتري ومنهج تحليل المضمون في سياق منهج دراسة الحالة، واتخذت من قائمة رؤوس الموضوعات العربية الكبرى لشعبان عبد العزيز خليفة ومحمد عوض العائدي معياراً لرؤوس الموضوعات المقننة. اشتملت عينة الدراسة على عناوين الكتب العربية الواردة ضمن الاستشهادات المرجعية لأعمال المؤتمر، وركزت الباحثة على استقاء رؤوس الموضوعات من تلك العناوين ورصدت مدى تكرارها في عناوين الاستشهادات المرجعية وقامت بتحليلها. من أهم نتائج الدراسة: تأكيد خضوع عينة الاستشهادات المرجعية لقانون برادفورد للتشتت، والكشف عن أهم مجالات التداخل الموضوعي في مجال المكتبات. ومن أهم التوصيات: ضرورة التزام الباحثين بصياغة عناوين أعمالهم برؤوس موضوعات مقننة، وضرورة تضمين رؤوس الموضوعات المرشحة للتقنين في قوائم رؤوس الموضوعات ذات العلاقة عند تحديث طبعاتها، وتدريب المكتبيين في مجال التكنولوجيا والإدارة والتربية والتعليم.
Keywords: الاستشهادات المرجعية -- رؤوس الموضوعات -- الاتحاد العربى للمكتبات ( اعلم )